Sistem Informasi Manajemen Sistem Informasi Manajemen Pengujian Laboratorium Teknik Sipil Universitas Wiraraja Berbasis Web Dengan Metode Research And Development (R&D) - Ramadhani, Dea Nurika; Iddrus, Iddrus (Fakultas Teknik, Universitas Wiraraja, 2025)
The use of information technology in higher education has become a strategic factor in supporting transformation and improving the quality of services, including in the management of civil engineering laboratories. Material testing such as paving, concrete cubes, and concrete cylinders is an essential part of civil engineering laboratory activities that require accurate, efficient, and easily accessible recording and reporting processes. However, at Universitas Wiraraja, data management for testing activities is still carried out manually, leading to frequent recording errors, delays in reporting, and difficulties in tracking the status of tests. This research aims to develop a Web-Based Management Information System for Civil Engineering Laboratory Testing at Universitas Wiraraja using the Research and Development (R&D) method. The R&D method involves several stages, including potential & problems, literature study, data collection, system design, design validation, system trial, system revision, and system implementation. The system is designed to replace the manual process and improve the speed, accuracy, and integration of laboratory data management. The results of the study show that the developed information system significantly improves the laboratory's operational efficiency. It reduces recording errors, accelerates data entry and retrieval processes, and simplifies the generation of test reports. The system was evaluated through direct user testing in the laboratory, and the results indicate that the system functions well and is wellreceived by users. Additionally, it enables real-time sample tracking and flexible data access within the local campus environment without relying on external internet connections, ensuring data security and confidentiality.